Peningkatan Kualitas Laporan Keuangan : Pelatihan SAK-EMKM & Aplikasi KLEDO Pada Industri Keripik Batang Pisang Desa Cimenyan - Fia Dialysa (Universitas Maritim AMNI Semarang, 2023)
The background is financial reports have not complied with accounting standards and no digital-based financial system innovations. This will affect banking decisions to provide financing assistance and MSMEs difficulties in sustaining their business. This service aims to improve the quality of financial reports and digital-based financial innovation (fintech) then MSMEs can be highly competitive and continuously reduce banana stem waste in Cimenyan. The method used is training & mentoring so that more